Epigenetic regulation of circ-HIPK3, circ-PVT1, miR-25, and miR-149 in radiosensitivity of breast cancer - Elahe Abdollahi; Hossein Mozdarani (Elsevier, 2023)
Assessing the radiosensitivity of cells before administering radiation therapy (RT) to individuals diagnosed with breast cancer (BC) can facilitate the selection of appropriate treatment regimens and minimize the incidence of adverse side effects in patients undergoing radiation exposure.In this research, blood samples were obtained from 60 women who had been diagnosed with Invasive Ductal Carcinoma (IDC) Breast Cancer. The average age of the patients was 47 ± 9.93. Additionally, the study incorporated 20 healthy women, with an average age of 44.43 ± 6.7. A standard G2 assay was conducted to predict the cellular response to radiation. Out of the 60 samples, the G2 assay identified 20 patients with breast cancer who exhibited radiosensitivity. Hence, molecular investigations were ultimately conducted on two equivalent cohorts comprising 20 subjects each, one with and the other without cellular radiosensitivity. The expression levels of miR-149, miR-25, circ-PVT1, and circ-HIPK3 in peripheral blood mononuclear cells (PBMCs) were evaluated using quantitative polymerase chain reaction (qPCR). Receiver Operating Characteristic (ROC) curves were used to evaluate the sensitivity and specificity of the RNAs. An analysis using binary logistic regression was performed to investigate the relationship between RNAs and both BC and cellular radiosensitivity (CR) in patients with BC.The findings revealed a significant upregulation of Circ-HIPK3 and circ-PVT1 in individuals diagnosed with BC. The levels of Circ-HIPK3 and Circ-PVT1 were found to be directly associated with CR in BC patients. The analysis of the ROC curve demonstrated that circ-HIPK3 and circ-PVT1 exhibit favorable specificity and sensitivity in accurately predicting both BC and CR in patients with BC. The findings from the binary logistic regression analysis demonstrated that circ-HIPK3 and circ-PVT1 were effective predictors of both BC and CR. The ROC curve and binary logistic regression analyses provide evidence that miR-25 is a reliable predictor for BC patients exclusively.Our research has demonstrated that circ-HIPK3, circ-PVT1, and miR-25 may be involved in BC regulatory processes. The circular RNAs Circ-HIPK3 and circ-PVT1, as well as miR-25, among other significant biomarkers, could potentially serve as promising biomarkers for predicting BC. Furthermore, Circ-HIPK3 and circ-PVT1 have the potential to serve as biomarkers for predicting CR in BC patients.